Sistema híbrido solar e geotérmico para aquecimento de água e condicionamento térmico - Soares, Roberta Mulazzani Doleys (2021)
The main goal of this work was to develop and evaluate a hybrid system for water heating and environmental thermal conditions. The project was divided in three subsystems: the first one consists of a set of brises plates with solar capture and named herein as SCS; the second one was a geothermal subsystem with buried pipelines and defined as SCG; the third was an association of the second one subsystem with a radiant floor, named as thermal module subsystem (SCM), which result in autonomous and adaptable system for environment climatization for both situations, heat or cold. Besides of supplying heat water. It was chosen the common typology of brises used in buildings, according to the solar orientation. The hybrid system was analysed following the Case 600 of the ASHRAE Standard 140 for the climatic conditions of Santa Maria/RS/Brazil. Data of the thermal comfort as: the energy efficiency; the water and environmental temperatures were obtained through computer simulations using the software EnergyPlus. The first model simulated was characterized as a standard one using the traditional building materials from region and called isolated base case. With the results it was possible to conclude that the SCS subsystem reached the purpose of heating water for morning and night baths, which values varied from 20°C to 28°C and 23°C to 37°C, respectively. Furthermore, this subsystem promoted the reduction of heat discomfort in environment temperature for about 16% to 25%. Nonetheless, the system had little capacity to minimize the discomfort for cold temperature, showing dependence from solar orientation; from the aid promoted by the pump heat and the collected area from SCS. The SCG system promoted a reduction of the heat discomfort between 5% to 11%. In this context, the study of the standard system proved to be important to characterize the wrapping for effectiveness of the subsystems about the thermal behaviour, mainly due to the reduction of thermal exchanges. In the isolated case, the hybrid system reached a reduction of cold discomfort between 15% to 76%. The heat pump coupled increased the discomfort reduction potential for cold, reaching values between 32% to 86%. The use of the SCG generated a reduction in heat discomfort, ranging values from 69% to 79%, and with the participation of the SCS there is a reduction of 89% to 93% of the discomfort in the hot periods. For electricity consumption, if you compare the hybrid system and the heat pump with a split condition and electric shower, there is a saving of 62% to 80%. It was found that the proposed integrate system was viable solution for this region or in similar climatic conditions, contributing positively to thermoenergy issues and becoming a more applicable alternative to the better of thermal performance of buildings.